Feasibility study of LNG pre â cooling system using carbon Dioxide as a refrigerant - Norshahida, Rahman (2011)
Refrigeration is a process of removing heat from a colder medium. By using the latent heat properties of refrigerant, the heat will be rejecting to a warmer medium. The basic of requirements for the refrigeration are the compressor, chiller, expansion valve and also condenser. In the LNG industry, refrigeration plays a major part. The aims of this research are to compare the difference of refrigerants used in pre-cooling system. The refrigerants that used in this research are propane and carbon dioxide. Another part that must be focused on this research is the refrigerantsÃ¢ÂÂ parameters which are most important consideration for approving that the carbon dioxide can be replacing the propane as a refrigerant that can be used soon in pre-cooling loop system. A simple model of propane refrigeration loop is used to create a steady state simulation using Aspen HYSYS 7.0 process simulator. By having a valid data from the propane loop, a simulation can be continued by replacing composition from propane to carbon dioxide. The same model constructed in the loop, but the other conditions must be changed to make it suitable and converged with the new refrigerant. The composition of refrigerant in the loop is still same 1, showing the purification of the component. The result shows the coefficient of performance (COP) for propane is 1.73 and carbon dioxide is 4.78. For the value of compressor duty using carbon dioxide is lower than the original loop, which the value is 96.7808 kW and propane duty is at 162.938 kW. Lastly, in terms of the costing of compressor using carbon dioxide is only at $ 54320 / yr which lower compared to compressor cost for propane is $ 91280 / yr. At this stage, we can conclude that the low duty, make the cost is low and this project will be more save. So, from this research, it can be conclude that it is successful because the main objective for replacing carbon dioxide as refrigerant has been achieved where the COP of carbon dioxide is higher than COP of propane.